2007
DOI: 10.1038/labinvest.3700627
|View full text |Cite
|
Sign up to set email alerts
|

Androgens influence expression of matrix proteins and proteolytic factors during cutaneous wound healing

Abstract: Excessive proteolytic activity is a feature of chronic wounds such as venous ulcers, in which resolution of the inflammatory response fails and restorative matrix accumulation is delayed as a consequence. The inflammatory actions of native androgens during the healing of acute skin wounds have lately been characterized. We have now investigated the hypothesis that such activities may impact upon the balance between anabolic and catabolic processes during wound healing. We report that wound deposition of both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 49 publications
3
23
1
2
Order By: Relevance
“…MMP-2 is implicated in the pathogenesis of chronic leg 31 and diabetic foot 32 ulceration and in the impairment of healing by aging 15 and androgens, 33 while limiting the activity of MMP-2 (and MMP-9) has been proposed as a mechanism by which healing might be improved. 34 We thus inferred that estrogens might create a degradative environment in the dermis that may contribute to delayed repair following subsequent injury, and indeed, we found that the similar induction of MMP-2 activity in day 3 wounds in estrogen-treated animals was accompanied by reduced accumulation of collagen.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-2 is implicated in the pathogenesis of chronic leg 31 and diabetic foot 32 ulceration and in the impairment of healing by aging 15 and androgens, 33 while limiting the activity of MMP-2 (and MMP-9) has been proposed as a mechanism by which healing might be improved. 34 We thus inferred that estrogens might create a degradative environment in the dermis that may contribute to delayed repair following subsequent injury, and indeed, we found that the similar induction of MMP-2 activity in day 3 wounds in estrogen-treated animals was accompanied by reduced accumulation of collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies by Ashcroft and colleagues, using surgical or chemical castration, have found that androgens were able to inhibit cutaneous wound healing, possibly by modulating inflammatory responses, matrix deposition, and keratinocyte function (1,(8)(9)(10). However, the in vivo role of androgens/AR signals in different cell types involved in the wound-healing process remains unclear.…”
Section: Introductionmentioning
confidence: 95%
“…The rate of collagen deposition is determined by the balance of collagen synthesis and degradation. Interestingly, the activity of MMP-1 (collagenase I) and MMP-13 (collagenase III) was reduced in castrated rats in the later stages of wound healing (9). Because macrophages express several proteinases and their activators/inhibitors (46)(47)(48)(49), it is possible that macrophage AR promotes the expression or activation of proteinases to enhance collagen degradation.…”
Section: Figurementioning
confidence: 99%
“…Although these effects were suggested to occur via DHEA conversion to estrogens (24), our findings suggest an androgenic effect in the stimulatory action of DHEA on procollagen A1 expression, in the context of a normal hormonally deprived skin model. Supporting this explanation, studies in animal models and in the human have demonstrated the stimulatory effect of testosterone and DHT on dermal collagen content (32,58,59), whereas, in wound healing, the role of androgens could be different (60,61). However, neutral or a beneficial role of androgens in stimulating the production of type 1 collagen protein have been described in scratch-wounded and intact rat dermal fibroblasts, respectively (59).…”
Section: Dermismentioning
confidence: 93%